Integrating Zinc Cream-Chitosan and Cadexomer Iodine for Treating Infections in Diabetic Foot Ulcers: A Case Report - Intan Asri Nurani; Rizki Hidayat; Bahri, Khairul; Fajar, Kana (Global Indonesia Health Care (GOICARE), 2024)
Background: The incidence of Diabetes Mellitus is reported to be increasing. These wounds can be challenging to heal and may lead to amputation if not treated appropriately. Treating wound infection requires careful antiseptic wound washing, removal of dead tissue, and the use of topical antimicrobial dressings. Aim in this case, we reported a case of diabetic foot ulcer infection used zinc cream-chitosan and cadexomer iodine. Case: A 76-year-old woman with a history of diabetes mellitus presented to the Wound, Ostomy and Continence Care Department at Wocare Indonesia in Bogor with an infected diabetic foot ulcer. The wound is classified as unstageable due to the presence of 100% slough tissue covering the entire wound bed. Additionally, there is erythema and oedema in the wound area, moderate purulent exudate, and slight bleeding. The wound emits an odour detectable within a distance of less than one meter. ABPI 0.67. The wound local infection assessment used NERDS and infection used WIFi classification. The primary dressing used for wound care was zinc cream-chitosan and cadexomer iodine 0.9%. Dressing changes were performed once every three days. Conclusion: The study examined the effectiveness of using zinc cream-chitosan and cadexomer iodine 0.9% to treating infection in diabetic foot ulcer wounds. The NERDS score decreased from 5 to 3, and the WIFi Classification decreased from 4 to 2, indicating an improvement in wound healing and patient quality of life with diabetic foot ulcers.